1996
DOI: 10.1017/s0022215100134553
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral choanal atresia in siblings – a rare occurrence

Abstract: The genetic aspects of choanal atresia have not been clearly defined though it is probably a multifactorial trait as in cleft lip and cleft palate. The appearance of the condition in both single and successive generations supports this contention.Choanal atresia can occur as an isolated anomaly, but is more commonly associated with one or more concomitant congenital anomalies. In this report two sisters both in their teens presented with unilateral choanal atresia as an isolated anomaly. Endoscopic trans-nasal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…14 More commonly, CA is found to occur sporadically and to recur infrequently in siblings and in subsequent generations. [14][15][16] abnormalities were noted, viz., anteposed anal opening and a systolic murmur. Subsequently, two-dimensional echocardiography detected arterial septal defect (ASD).…”
Section: Discussionmentioning
confidence: 99%
“…14 More commonly, CA is found to occur sporadically and to recur infrequently in siblings and in subsequent generations. [14][15][16] abnormalities were noted, viz., anteposed anal opening and a systolic murmur. Subsequently, two-dimensional echocardiography detected arterial septal defect (ASD).…”
Section: Discussionmentioning
confidence: 99%
“…While familial cases of choanal atresia have been reported, suggesting monogenic inheritance with autosomal dominant and autosomal recessive modes of transmission, the majority of cases are sporadic. [11][12] There are a few reported cases of bilateral choanal atresia among siblings. Sadek 2 recently described six cases of bilateral bony choanal atresia among siblings with associated abnormalities who were offspring of consanguineous marriages.…”
Section: Discussionmentioning
confidence: 99%
“…Some previously published studies have suggested that choanal atresia tends to occur sporadically and to recur infrequently in siblings and in successive generations [Bhattacharyya and Lund, 1996; Gershoni-Baruch, 1992; Skolnik et al, 1973]. Other studies have suggested single gene models that include both autosomal dominant and autosomal recessive transmission [Gershoni-Baruch, 1992].…”
Section: Introductionmentioning
confidence: 99%